2005
DOI: 10.1111/j.1440-1754.2005.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in an infant with pyloric stenosis

Abstract: 'Simultaneous occurrence of pyloric stenosis and multiple small gallstones has been reported only once previously, though jaundice is frequently observed in patients with congenital hypertrophic pyloric stenosis'. Gallstone disease is rare in infancy. 1-5 Usually, some underlying aetiology is identifiable when gallstones are diagnosed in younger children, for example, total parenteral nutrition, ileal resection, sepsis, dehydration etc. 2,5,6 However, only one case of gallstones with pyloric stenosis (PS) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cholelithiasis is rare in infancy, but several predisposing factors to cholelithiasis in infancy have been identified, such as prematurity, prolonged fasting, parenteral nutrition, use of furosemide, ceftriaxone therapy, sepsis, or dehydration . It was reported that pyloric stenosis, Bartter syndrome and PHA are related to cholelithiasis in infancy, a condition in which dehydration is likely to develop. In the current case, those risk factors were not present, except for possible chronic dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Cholelithiasis is rare in infancy, but several predisposing factors to cholelithiasis in infancy have been identified, such as prematurity, prolonged fasting, parenteral nutrition, use of furosemide, ceftriaxone therapy, sepsis, or dehydration . It was reported that pyloric stenosis, Bartter syndrome and PHA are related to cholelithiasis in infancy, a condition in which dehydration is likely to develop. In the current case, those risk factors were not present, except for possible chronic dehydration.…”
Section: Discussionmentioning
confidence: 99%